IMPLEMENTATION OF PUBLIC SPORTS DEVELOPMENT EVENTS AMONG WOMEN IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS - N. A. X Udayberdieva (Web of Journals Publishing, 2024)
Reforms in the field of propaganda and involvement of women in physical education and mass sports, the formation of a healthy lifestyle, strengthening the desire for self-expression are urgently needed and require a high-quality and scientifically based solution. In this regard, the ongoing study on the development and implementation of a mechanism for popularizing and involving women in mass sports proves its relevance and will serve as a solution to the priority tasks set in regulatory documents and acts.
Keywords: mass sports, health, healthy lifestyle, development, physical education, attraction.